A longitudinal analysis of the completeness of maternal HIV testing, including repeat testing, during pregnancy, and the predictors thereof, in Mitchell’s Plain, Cape Town - De Beer, Shani (Department of Public Health and Family Medicine, 2020)
HIV testing during pregnancy is the gateway to the HIV-related services that are part of the prevention of mother-to-child transmission (PMTCT) cascade. The virtual elimination of vertical HIV transmission cannot be achieved without universal antenatal care (ANC) HIV testing. Furthermore, women are at an increased risk of HIV infection and subsequent mother-to-child transmission (MTCT) during pregnancy. Emphasis has thus been placed on repeat testing during pregnancy among women who have a HIV-negative result at their first ANC test. Very little has been published on the current uptake and adherence to antenatal and repeat HIV testing in sub-Saharan Africa (SSA) countries. In line with the World Health Organization Guidelines, the Western Cape Prevention of Mother-to-Child Transmission of HIV (PMTCT) Clinical Guidelines in 2014 recommended a repeat HIV test between 32 - 34 weeks gestation and again at delivery in addition to testing at “booking” (< 20 weeks gestation), meaning that there were three “testing windows” during which pregnant women not previously diagnosed as HIV-infected should undergo testing. Between 2013 and 2016 the Closing the Gaps study established an electronic PMTCT register (e-register) that consolidated routine care data from a primary healthcare facility and its secondary and tertiary referral sites in Cape Town, South Africa. This provided a single longitudinal record, from antenatal care to delivery, for each pregnant woman which enabled the longitudinal assessment of maternal HIV testing uptake and treatment. Utilizing these data, we conducted a retrospective sub-analysis investigating the implementation of PMTCT HIV testing guidelines (until delivery), in Cape Town, for the period 1 July 2014 - 31 December 2016. The main objectives of the study were to assess the coverage and timing of initial HIV testing during pregnancy, the completion of HIV testing at “booking” and within the recommended testing windows (including delivery), HIV prevalence and incidence at the recommended testing windows, and the predictors of missed testing opportunities. The research protocol (Part A) was designed to describe the proposed significance, objectives and methodology of the study. The literature review (Part B) critically evaluated available literature on: antenatal and repeat HIV testing proportions, HIV positivity, the feasibility and acceptability of repeat iv testing, and the predictors of testing completeness within different SSA countries, for the period 2010 - June 2018. Its aim was to inform this study. The need for post-Option B+ implementation, longitudinal studies that analyze antenatal and repeat HIV testing coverage and implementation within SSA was identified. In Part C I present the methods, results and interpretation thereof for the analysis of individual-level, longitudinal, maternal HIV-testing patient data from the Closing the Gaps study e-register as a manuscript to be submitted for publication. Among 8558 women who delivered at either the primary care facility or its referral sites, 7213 were not diagnosed HIV-positive prior to their first visit and thus eligible for testing in pregnancy. Among these women, 91% received ≥1 HIV test and 85% “booked” >5 days before delivery with 98% testing completeness at “booking”. Only 49% of women eligible for testing “booked” ≤22 weeks gestation. Among women that “booked” ≤22 weeks gestation who weren’t diagnosed HIV-positive before delivery and delivered >5 days after the start of the third trimester, 10% received tests in all three recommended windows. Thirty-one percent of women that had not been diagnosed HIV-positive before delivery had an uncertain (i.e. last tested ≥3 months before delivery) or unknown (i.e. never tested) HIV status after delivery. Out of the women that had a known HIV status at delivery, 21% were HIV-positive of whom 95% were known HIV-positive before current pregnancy and 4% were diagnosed at “booking”. Overall, HIV incidence in those with ≥2 HIV tests during pregnancy/at delivery was estimated to be 0.2% between “booking” and delivery. Women who enrolled after 2014 were less likely to miss ≥1 of the three recommended tests (aOR: 0.70; CI: 0.55 - 0.90) and not test at delivery (aOR: 0.63; CI: 0.55 - 0.71) compared to those who enrolled in 2014. Conclusion: In our study, HIV testing completion at “booking” was high, but women tended to “book” late during pregnancy resulting in late initial testing and missed opportunities for early HIV diagnosis. Implementation of repeat HIV testing is poor, particularly at delivery. HIV incidence between first negative ANC test and delivery is very low and therefore future studies to assess the most cost-effective number and timing of HIV tests, and feasibility of implementation, should be considered. Overall, maternal HIV testing within the PMTCT programme in Cape Town has matured post 2014 with improved implementation over time.